ANALISIS EKSISTENSI PERAN APARAT PENGAWASAN INTERN PEMERINTAH (APIP) DENGAN PARADIGMA SEBAGAI KONSULTAN (STUDI KASUS PADA INSPEKTORAT KABUPATEN KEPULAUAN SIAU TAGULANDANG BIARO) - Novianty Trisye Sabaru; Ventje Ilat; Heince Ruddi Nicky Wokas (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2022)
The demands for an effective APIP role have changed since the presence of PP no. 12 of 2017 which expands the scope of APIP's role to provide confidence and consultancy. The change in the role of APIP makes APIP's function not only give confidence but also carry out consulting activities to help management provide professional input and consideration regarding the risks faced by the organization. The purpose of this study is to analyze the role of APIP after the paradigm shift as a Consultant in the Inspectorate of Kepl District. Siau Tagulandang Biaro, as well as analyzing the impact of APIP's role as a consultant contributed negatively in terms of weakening APIP's role as an Internal Auditor or contributing positively to providing consulting or mentoring services to OPD in carrying out tupoksi. The results of the research show that APIP's role as a consultant improves the quality of APIP as an internal government audit. As well as strengthening apip's role as a provider of confidence and consultation in local government supervision matters. The role of APIP also contributes positively to both the Inspectorate and Obrik. Where the new role helps Obrik through the current approach, namely problem prevention (preventive) instead of looking for problems. The obstacles faced by the Inspectorate related to the existence of the treatment of the role as a Consultant are limited human resources and budgets.